A condicionalidade em línguas indígenas brasileiras: uma análise tipológica-funcional - Lourenço, Fabiana Pirotta Camargo (Universidade Federal de São Carlos, 2023)
In Brazil, 274 indigenous languages are currently spoken by individuals belonging to 305 different ethnic groups, which reflect a great linguistic and typological diversity, each constituting a complex system, with specific sets of sounds, categories and structuring rules, (Seki,2000). These languages have become the object of study in many works dedicated to describing their syntactic, phonological or pragmatic aspects. However, it was observed that regarding conditional subordinate constructions, there is a lack of studies dedicated, in a more comprehensive way, to characterizing their expression in these languages, as well as in Brazilian Portuguese and in other languages. Bearing in mind this lack and relevance of the theme, the main objective of this work was to typologically describe conditionality, promoting a systematization of the conditional expression, adopting for this purpose the typological-functional method of analysis, in a group consisting of 42 Brazilian indigenous languages, distributed among 19 linguistic families. The determination of the languages that make up the corpus was based on the classifications elaborated from the works of Rodrigues (2013) and Moore (2011). For language analysis, samples of conditional constructions described in works such as articles, theses and dissertations were collected. These constructions were analyzed, observing mainly the types of markers and the associations between them for the expression of the conditional value. The main hypothesis of the research, which was confirmed in the results of the analysis, was that the conditional value, in Brazilian indigenous languages, is expressed by different elements, which can be by a conjunction, affix, particle, among others, and in a mostly compositional/multifactorial way, that is, from a combination of elements that refer to other linguistic categories, such as irrealis and modality, which play a significant role in conditional marking. Still, regarding the contribution of time stamping (past/non-past) to the distinction of the conditional senses of counterfactuality and potentiality, as well as Plungian (2005), a scale of unreality was established, in which the counterfactuals seem to be more representative of the irrealis, as they are more directly linked to unrealized situations. The work, finally, made it possible to survey shared patterns between languages with regard to the formal and semantic expression of conditionality. It is also expected that it has contributed to the area of Indigenous Linguistics, and to the descriptions already developed about conditional subordinates in this area.
Conditionality in brazilian indigenous languages: a typological-functional analysis
Keywords: Tipologia linguística; Condicionalidade; Línguas indígenas brasileiras; Linguistic tipology; Conditionality; Brazilian indigenous languages; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS INDIGENAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA